2014
DOI: 10.1177/0963721414533702
|View full text |Cite
|
Sign up to set email alerts
|

The Vividness of the Happy Face

Abstract: An emerging literature reveals that happy faces are vivid: They automatically and rapidly engage cognitive processing at many different levels. They do this in part because their form has evolved to take advantage of preexisting efficiencies in visual perception. In addition to "happy advantages" at the earliest stages of perception, perceivers add their own benefits, with both attentional and memory mechanisms appearing to favor happy faces. These effects exist because for humans, prosocial communication is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 32 publications
3
43
0
1
Order By: Relevance
“…However, for affective empathy, we did not hypothesise that these children would also show impaired affective empathy for happiness based on the previous studies [11,39]. Future research should aim to clarify the nature of affective empathy impairments in antisocial populations, especially as happiness may diffuse hostility and encourage prosocial behaviour [40].…”
Section: Discussionmentioning
confidence: 73%
“…However, for affective empathy, we did not hypothesise that these children would also show impaired affective empathy for happiness based on the previous studies [11,39]. Future research should aim to clarify the nature of affective empathy impairments in antisocial populations, especially as happiness may diffuse hostility and encourage prosocial behaviour [40].…”
Section: Discussionmentioning
confidence: 73%
“…For example, Smith and Schyns (2009) showed that happy and surprise expressions are recognised easier than sad, angry, fearful and disgust expressions, even over a wide range of viewing distances. However, according to a recent meta-analysis (Nummenmaa & Calvo, 2015; see also Becker and Srinivasan, 2014), the authors conclude that the robust happy advantage found in many studies with healthy individuals seems to reflect its affective valence and not lowlevel visual features. Nevertheless, future research should carefully control for the visual conspicuity of the facial stimuli (e.g., luminance, contrast, spatial frequency) in order to disentangle if the dissociations in processing emotional social stimuli should solely be attributed to emotional factors, and whether visual information has an additive effect in studies using clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the human fear expression, argued to have evolved its current form to resemble a babyish appearance, thereby eliciting a functional caretaking response from others (Marsh, Adams, & Kleck, 2005). Likewise, happy facial expressions are argued to have evolved because they efficiently diffuse impressions of threat by perceivers from a distance; happy expressions also benefit from a preattentive recognition advantage that emerges in as little as 27 milliseconds, presumably exploiting older, more basic perceptual mechanisms (Becker & Srinivasan, 2014). …”
mentioning
confidence: 99%